Role and Adverse Effects of Premedication for Reducing Pain and Discomfort during Fiberoptic Nasal Pharyngoscopy and Laryngoscopy - Acharya, Anup; Singh, Madan Mohan; Pandey, Bhuwan Raj; Pandit, Shiv Bhushan; Bartaula, Suman (Journal of Universal College of Medical Sciences, 2020)
INTRODUCTION: Fiberoptic nasal endoscopy is a common procedure. Pretreatment with many drugs has been tried to decrease discomfort and pain related to the procedure. It was our effort to study whether they are effective in reducing pain and discomfort of the procedure. MATERIAL AND METHODS: It was a four-armed triple blind randomized controlled trial. Block randomization was done. Four arms were pretreated with placebo, decongestant spray, local anesthetic spray, and combination of decongestant and local anesthetic spray. Discomfort of pretreatment, discomfort of the procedure, pain due to procedure, ease of procedure and adverse effects were recorded by visual analogue score and analyzed by non-parametric tests. P value less than 0.05 was considered statistically significant. RESULTS: There were 40 participants in each wing making a total of 160. There were 79 males and 89 females. Discomfort of pretreatment was significantly higher is groups treated with lidocaine spray alone or in combination (p<0.001). Discomfort due to procedure was lowest in group pretreated with placebo (p=0.009) and pain was comparable throughout the groups (0.15).The procedure of nasal endoscopy was easiest in group pretreated with decongestant spray (p=0.02). Adverse effect was highest in form of burning sensation and pain in groups treated with lidocaine (p<0.001). CONCLUSION: Lidocaine spray caused a lot of discomfort in form of pain and burning sensation and was not able to decrease pain or discomfort, alone or in combination with decongestant, related to fiberoptic nasal endoscopy. Decongestant, however, made the procedure easier.